Enhancing students’ language skills through direct instruction: Pedagogical adaptation to social and institutional contexts - Fatmaya Anisa Rahmania (Asian Journal Collaboration of Social Environmental and Education, 2026)
Background: Arabic is a local content subject that poses considerable challenges for students, due to their diverse educational backgrounds. Therefore, the selection of an appropriate learning model is a crucial factor in achieving instructional objectives. One model applied is the Direct Instruction learning model, which emphasizes the direct and systematic delivery of learning materials. This study aims to analyze the optimization of Arabic language learning through the Direct Instruction model in Arabic language instruction. Methods: This study employed a descriptive qualitative field research design grounded in a post-positivist paradigm. Data were collected through non-participant observation, in-depth interviews, and document analysis to capture the learning process and instructional practices. Data analysis followed an interactive model consisting of data collection, data reduction, data display, and conclusion drawing to ensure systematic interpretation and credibility of the findings. Findings: The findings indicate that the implementation of the Direct Instruction model in Arabic language learning begins with preparatory activities, including the development of Lesson Plans/Rencana Pelaksanaan Pembelajaran (RPP), attendance recording, and the organization of learning materials. During the core stage, the teacher delivers the material directly, while the final stage involves evaluation through written tests, oral tests, and practical exercises. Conclusion: Overall, the study concludes that the Direct Instruction model is effective in improving students’ understanding and Arabic language skills by providing a structured, systematic, and adaptive learning process. Its implementation not only creates a more conducive and inclusive learning environment but also demonstrates relevance as a pedagogical response to diverse student backgrounds and limited instructional contexts, emphasizing the importance of aligning teaching strategies with institutional and social conditions to optimize learning outcomes. Novelty/Originality of this article: The study reveals that the use of the Direct Instruction model enhances students’ enthusiasm and comprehension in Arabic language learning, contributing to the optimization of direct instruction–based learning methods at the junior high school level.